OSS and FRAND: Complementary Models for Innovation and Development - Lindberg, Van (Science and Technology Law Review, 2019)
In The Truth About OSS-FRAND, David Kappos and Miling Harrington argue that it is both permissible and desirable to charge FRAND (“fair, reasonable, and non-discriminatory”) royalties on open source software (“OSS”) that is incorporated into a standard containing standard-essential patents (“SEPs”). In arguing that OSS and FRAND are compatible in this way, Kappos and Harrington take the position that when standard-setting communities intentionally incorporate OSS-licensed code into a standard, it is the royalty-free status of open source that should give way, not the payment of the FRAND-based royalty. This Comment examines the Open Source Definition (“OSD”), the text of OSD-compliant licenses, and discussions surrounding their creation to conclude, contrary to Kappos and Harrington, that essentially every OSD-compliant open-source license includes a royalty-free patent grant, which precludes the imposition of FRAND-based royalties. Standard-setting organizations that wish to charge FRAND royalties ultimately have the same option that commercial enterprises have when dealing with open source: respect OSD licenses, including their implied royalty-free patent grants, or create an alternative commercial license that conveys no patent grant.